Transitions in and out of Unemployment among Young People in the Irish Recession - Kelly, Elish (OECD Publishing, 2013)
Young people have been hit hard by unemployment during the Irish recession. While much research has been undertaken to study the effects of the recession on overall labour market dynamics, little is known about the specific effects on youth unemployment and the associated challenges. This paper attempts to fill this gap by comparing the profile of transitions to work before the recession (2006) and as the economy emerged from the recession (2011). The results indicate that the rate of transition of the youth from unemployment to employment fell dramatically. The fall is not due to changes in the composition or the characteristics of the unemployed group but to changes in the external environment, which implied that the impact of certain individual characteristics changed over the course of the recession. In particular, for youth, education and nationality have become more important for finding a job in Ireland
Keywords: Employment; Economics; Ireland